Two new species of the genus Xizicus, 1993 (Orthoptera: Tettigoniidae: Meconematinae) from Xizang, China - Jiao, Jiao; Shi, Fu-Ming; Gao, Jia-Guo (Zootaxa, 2013)
In this paper two new species of the genus Xizicus from Xizang, China are described, Xizicus (Axizicus) spinocercus Jiao & Shi sp. nov. and Xizicus (Axizicus) xizangensis Jiao & Shi sp. nov. The type specimens are deposited in the Museum of Hebei University.